Design and Application of a Smart Home System Based on Internet of Things - Das, Resul; Ababaker, Taha Abdullah Ababaker (My University, 2021)
The Internet of Things plays a critical role in smart home systems techniques. A smart home system provides a major change in the life of humans that gives home appliances intelligent operation. This encouraged us to create a solution for controlling certain home appliances, such as door and lights. This system is used to monitor the status of the door, window, temperature, humidity, and measuring distance by using various sensors such as IR, DHT22, and ultrasonic sensors. NodeMCU ESP8266, Relay module, and Arduino Uno have been used as the main parts in this paper. The system presented in this paper able to monitor and control home appliances from any corner of the world at any time and efficiently utilize the power by properly controlling the appliances. Ubidots IoT platform and Blynk application were used to check and read data from sensor modules placed in the home and, also to control home appliances by turning ON/OFF relay switches such as door and lights. The paper also focused on protecting user's data by using the AES method to ensure that a system encrypts and encodes Wi-Fi information before sending it to a destination, eventually, to restore the original data, it decrypts and decodes the data.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği; Telekomünikasyon